Urgensi Pemikiran Filsafat Pendidikan Islam KH. Hasyim Asy’ari dalam Kitab Adabul Alim Wal Muta’alim di Pondok Pesantren Sunan Gunung Jati - Yulqowin, Ilma; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
The term philosophy of Islamic education refers to an understanding of Islamic education from a philosophical point of view. In the world of Islamic education, one of the main resources of Islamic Boarding Schools in an effort to produce a scholar is the classical book. The classic book that is familiar in Pondok Pesantren about education is the book Adabul 'Alim wa al Muta'alim, by the great Indonesian scholar Hadratussyaikh Hasyim Asyari, expertise in the fields of hadith, Sufism, and philosophical thinking determines the quality of his thinking, to express philosophical thoughts about Islamic education, KH. Hasyim Asy'ari expressed his views in a book entitled Adabul Alim Wal Muta'alim. KH Hasyim Asy'ari's thoughts in the book Adabul Alim wal Muta'alim are very relevant and in accordance with educational values. This is because the book teaches the principles of education based on adab, morals, and the blessing of knowledge, which is the core of the tradition and education system of pesantren, namely the emphasis on adab and morals. The philosophy of education in Hasyim Asyari's thought is to prioritize akhlaqul karimah.